2020
DOI: 10.48550/arxiv.2012.07537
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

About the Pressure-Induced Superconducting State of Europium Metal at Low Temperatures

Abstract: In PRL 102, 197002 (2009), it was reported that Eu becomes superconducting in the pressure and temperature range [84-142GPa], [1.8-2.75K]. The claim was largely based on ac susceptibility measurements. Here I point out that recently reported ac susceptibility measurements on a hydride compound that appears to become superconducting near room temperature (Nature 586, 373 (2020)) call the results for Eu into question. It is suggested that the experiments on Eu should be repeated to validate or rule out the claim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…To d portant points are addressed in the d in the hydrogen sulfur system, the a complex superconducting behavio sures with a change in both crysta stoichiometry. It is almost impossibl the complex superconducting behavi experimental techniques, as reporte ous experiment by Drozdov et al [ the crystal structure and stoichiomet gen sulfur system under high pressur alyzed by the reported first-principl based on density functional theory (D known that H2S is the only known sta in the H-S system at ambient pressur dicted that H2S is stable below 43 G poses into H3S and S above this pres Except for H3S, other hydrogen-ri tries were also reported to be stable and the superconducting critical te calculated for various H-S compound with our experimental results, for temperature Tc phase below 140 G retically calculated Tc of the vario tries H-S phase may quantitatively low-Tc data [24,25]. It is propos H-S stoichiometries may be mainly the measured superconductivity of t low 140 GPa.…”
Section: The Measured Raw Datasupporting
confidence: 71%
See 1 more Smart Citation
“…To d portant points are addressed in the d in the hydrogen sulfur system, the a complex superconducting behavio sures with a change in both crysta stoichiometry. It is almost impossibl the complex superconducting behavi experimental techniques, as reporte ous experiment by Drozdov et al [ the crystal structure and stoichiomet gen sulfur system under high pressur alyzed by the reported first-principl based on density functional theory (D known that H2S is the only known sta in the H-S system at ambient pressur dicted that H2S is stable below 43 G poses into H3S and S above this pres Except for H3S, other hydrogen-ri tries were also reported to be stable and the superconducting critical te calculated for various H-S compound with our experimental results, for temperature Tc phase below 140 G retically calculated Tc of the vario tries H-S phase may quantitatively low-Tc data [24,25]. It is propos H-S stoichiometries may be mainly the measured superconductivity of t low 140 GPa.…”
Section: The Measured Raw Datasupporting
confidence: 71%
“…[22]) show a very significant change in slope across the transition, similar to what such data look like for the element europium at low temperature [23]. I have suggested that this implies that the published data for ac susceptibility of CSH are invalid [24][25][26]. Instead, the authors of ref.…”
Section: The Measured Raw Datamentioning
confidence: 62%
“…The facts discussed above raised questions in my mind about the validity of the magnetic susceptibility measurements presented both for CSH [1] and for Eu [10]. I wrote and published a paper raising these questions in late 2020 [19,20]. Other developments are discussed in the forthcoming sections.…”
Section: The 53rd Superconducting Elementmentioning
confidence: 99%
“…On November 19 and November 21, 2020, I sent a copy of my paper [19] commenting on the Eu paper [10] to three of Mathew Debessai's coauthors, asking for comments. One of them responded "I don't think it is appropriate to level such a serious accusation against Debessai", another responded that I "create with the reader the impression that Mathew may have manipulated the data" and "I am very disappointed and more than a little angry.…”
Section: Subsequent Attempts To Obtain Raw Data For Eu and Ultimate S...mentioning
confidence: 99%
See 1 more Smart Citation